Level Berpikr Anak Tunagrahita Ringan dalam Menyelesaikan Masalah Matematika Siswa Sekolah Alam Mahira Bengkulu Berdasarkan Taksonomi SOLO - Harmudianto Harmudianto; Wahyu Widada; Zamzaili Zamzaili (Jurnal Pendidikan Matematika Raflesia, 2019)
Tunagrahita were a terminology to called the children with mentally retarded conditions. This conditions caused these children having difficulties at least on four areas, related with attention, memory, language, and academics. This research’s aims to find out how the cognitive thinking characteristics of students of Debile of Tuna Grahita at the Mahira Alam School are based on SOLO Taxonomy. This research were descriptive qualitative with field research. Research’s subject which were the students of Mahira Alam School as much as 3 students. Data obtained used by observation, task-based interview, and documentation. The result showed that used 5 questions that have been made by a level of structural problems, there were only two students who were tend to have the same response or relatively the same answer, while the questions with the Relational level can be solved by one of debile of Tuna grahita. However, intelligence and language skills both reading and pronunciation are still inadequate.